Bone marrow involvement in pediatric malignancies: a comparison study of Positron emission tomographycomputed tomography and bone marrow biopsy - Tezol, Özlem; Sağcan, Fatih; Özcan, Pınar Pelin; Çıtak, Elvan Çağlar (The Turkish Journal of Pediatrics, 2020)
Background and Objectives. The comparison of Positron emission tomography- computed tomography (PETCT) and bone marrow biopsy (BMB) modalities in detecting bone marrow disease is an up to date research topic. In this study, we aimed to compare the results of PET-CT and BMB procedures in detecting bone marrow involvement in pediatric malignancies. Method. At the time of diagnosis, PET-CT imaging and BMB performed patients` data were evaluated, retrospectively. Malign diagnoses were Hodgkin's lymphoma in 23 (30.7%), non-Hodgkin's lymphoma in 20 (26.7%), neuroblastoma in 11 (14.7%), Ewing sarcoma in 10 (13.7%), Langerhans cell histiocytosis in 6 (8%), and rhabdomyosarcoma in 5 (6.6%) patients. Results. Bone marrow involvement was detected in 39 (52%) of 75 patients. Bone marrow involvement was identified by both PET-CT and BMB in 18 (46.1%) patients, by only PET-CT in 12 (30.7%) patients, by only BMB in 9 (23%) patients. The sensitivity of PET-CT was 66%, specificity was 75%, positive predictive value was 60%, and negative predictive value was 80%. Sensitivity, spesificity, positive and negative predictive values of PETCT were different in before mentioned malignancy groups. Conclusion. PET-CT may not have high sensitivity and specificity to identify bone marrow involvement for each type of cancer. The approach of using bone marrow biopsy and PET-CT as complementary modalities seems reliable.
Keywords: PET-CT; bone marrow involvement; pediatric malignancies